2014
DOI: 10.1111/1753-0407.12160
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma levels of the methylglyoxal in patients with newly diagnosed type 2 diabetes 初诊2型糖尿病患者血浆甲基乙二醛水平升高

Abstract: These findings suggest that increased plasma MG level is associated with the elevation of HbA1c and MDA in newly diagnosed T2DM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…The reactive dicarbonyls MG [57,58,59,60,61,62], 3DG [58,59,62,63,64] and glyoxal [57,59,60,62] are elevated in serum of diabetic patients alongside blood glucose levels. Protein bound AGEs and AGE free adducts are increased in experimental models of diabetes [18,39,65], and in diabetic patients in parallel with their precursors [66,67].…”
Section: Dicarbonyls In Diabetes and Relation To Diabetic Complicamentioning
confidence: 99%
“…The reactive dicarbonyls MG [57,58,59,60,61,62], 3DG [58,59,62,63,64] and glyoxal [57,59,60,62] are elevated in serum of diabetic patients alongside blood glucose levels. Protein bound AGEs and AGE free adducts are increased in experimental models of diabetes [18,39,65], and in diabetic patients in parallel with their precursors [66,67].…”
Section: Dicarbonyls In Diabetes and Relation To Diabetic Complicamentioning
confidence: 99%
“…AGEs have been consistently recognized to accumulate in the blood and tissues of diabetics, in cells isolated from those subjects, and in animal models of diabetes; they may or may not cause vascular complications, although a large body of literature highlights their fundamental role in the development of T2D‐associated vascular dysfunction . As depicted in Figure , these macromolecules and their precursors not only contribute to the induction of an oxidative environment but also directly affect several intra‐ and extracellular processes that impair vascular properties .…”
Section: Role Of Glycoxidized Macromolecules and Oxidized Lipids In Tmentioning
confidence: 99%
“…It has been reported that plasma concentrations of methylglyoxal in diabetic patients range from 4-400 µM. [7][8][9][10][11] However, the concentrations of methylglyoxal in the vitreous humor and in the retinal tissue have not been previously reported. Therefore, methylglyoxal doses were selected on the basis of the results of studies examining short-term impacts of methylglyoxal.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] An accumulation of methylglyoxal in the retina may contribute to the onset and progression of diabetic retinopathy. It has been reported that plasma concentrations of methylglyoxal in diabetic patients range from 4-400 µM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation